High temperature pyrolysis of sewage sludge: Synergistic effects of co-pyrolysis with rice straw and composite plastics wastes - Babayiğit, Elif; Alper, Dilek; Çokgör, Emine; Okutan, Hasan Can; Sarıoğlan, Alper; Çokgör, Emine; Okutan, Hasan Can; Sarıoğlan, Alper (Elsevier BV, 2024)
The synergistic effect of co-pyrolysis for the mixtures of sewage sludge (SS), rice straw (RS) and composite plastic wastes (PE&PP) has been investigated with the aim of high gas yields and hydrogen generation. In this context, the applicability of high temperature pyrolysis technology was evaluated at both rotary type batch reactor and rotating screw type continuous reactor operating under the industrially relevant conditions. Gas yields have been improved at increasing the operating temperatures up to 850 °C. The gas yield of 75.06 % with its H2 portion of 32.35 % has been achieved as the best results for continuous pyrolysis unit at pilot scale. Secondary reactions such as steam de-alkylation, steam cracking, water gas shift and so on were regarded as being responsible for the high gas yields when the primary products of pyrolysis, i.e. condensable vapors, were much exposed to the hot zones inside the reactor. The dehydration of organic components involving the loss of water may supply steam to create a reactive pyrolysis atmosphere. While the pyrolysis of sewage sludge and rice straw favors CO and CO2 formation due to the high oxygen contents of these feedstocks, more methane and light olefins were produced when the plastics were added to the feedstock blends. This was ascribed to the initially generated radicals from the decomposition of sewage sludge and/or rice straw that might promote the scission reactions of plastics towards volatiles. It was shown that high temperature pyrolysis can be applied to a variety of organic wastes such as rice straw, sewage sludge and waste plastics. Conversion of wastes to hydrogen fosters the circular economy by putting the disposal costs down and creates a new route on renewable hydrogen generation.
Keywords: Social sciences (General); H1-99; Q1-390; Science (General); Biomass; Sewage sludge; Plastics; Pyrolysis; Hydrogen; Research Article